2021
DOI: 10.1111/myc.13262
|View full text |Cite
|
Sign up to set email alerts
|

Race reporting and representation in onychomycosis clinical trials: A systematic review

Abstract: Onychomycosis is the most common nail disorder seen in clinical practice with a prevalence of 8.7%-13.8% in the United States (US). [1][2][3] There has been a trend towards increased racial and ethnic diversity in the United States, with current projections estimating that minority representation will exceed 50% of the population by 2044. 4 Demographic reporting and inclusion of diverse populations within clinical trials is critical to interpret treatment efficacy and prognosis for different groups. A systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 180 publications
(169 reference statements)
0
5
0
Order By: Relevance
“…In contrast, this same study found that Hispanic individuals (OR: 1.24; 95% CI: 1.17–1.31) were more likely to develop onychomycosis compared to White individuals. A 2021 systematic review of onychomycosis clinical trials demonstrated that only 32/182 (17.5%) of onychomycosis trials reported race and/or ethnicity, with only 1613/8270 (19.5%) non-white participants represented among studies between 2005–2020 [ 21 ]. Since our data, as well as previous research found that Blacks were more likely to have onychomycosis compared to other races, our study highlights the need to include more diverse participants in onychomycosis clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, this same study found that Hispanic individuals (OR: 1.24; 95% CI: 1.17–1.31) were more likely to develop onychomycosis compared to White individuals. A 2021 systematic review of onychomycosis clinical trials demonstrated that only 32/182 (17.5%) of onychomycosis trials reported race and/or ethnicity, with only 1613/8270 (19.5%) non-white participants represented among studies between 2005–2020 [ 21 ]. Since our data, as well as previous research found that Blacks were more likely to have onychomycosis compared to other races, our study highlights the need to include more diverse participants in onychomycosis clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other more common nail diseases, such as onychomycosis, with robust clinical trial data [21], previous smaller paronychia studies lacked characterization of races. We found approximately equal proportions of white (25.6%) and black (28.6%) patients diagnosed with paronychias.…”
Section: Discussionmentioning
confidence: 99%
“… 91 In a systematic review of race reporting in onychomycosis clinical trials, less than a fifth (17.5%; 32/182) of trials reported on race and/or ethnicity, with only one trial comparing treatment efficacy in different subgroups. 92 Therefore, treatment recommendations garnered from these trials should be interpreted with caution in patients of color.…”
Section: Treatmentmentioning
confidence: 99%